Limits of authenticity: How organizational politics bound the positive effects of authentic leadership on follower satisfaction and performance. Issue 6 (1st March 2021) - Munyon, Timothy P.; Houghton, Jeffery D.; Simarasl, Nastaran; Dawley, David D.; Howe, Michael
Abstract: The authentic leadership paradigm has been widely advocated as an effective leadership approach for organizations interested in promoting positive and ethical leader—member relations. Despite accumulating evidence concerning the positive follower effects of authentic leadership, research examining potential boundary conditions remains limited. The political influence theoretical perspective promises to shed new light on the effects of authentic leadership by proposing that authentic leadership may be less effective in political contexts, bounding its positive operation on followers. Specifically, we anticipate that organizational politics will erode the motivational power of authentic leaders on followers, reducing their ability to engender positive performance contributions in followers. We also predict that organizational politics will weaken the positive relationship between authentic leadership and job satisfaction by reducing the ability of employees to realize their goals at work. To explore these theoretical assertions, we incorporated a two‐study functional replication ( n 1 = 265; n 2 = 175) to ascertain how authentic leadership and organizational politics impact follower job satisfaction, organizational citizenship behavior (OCB), and task performance. We find that organizational politics consistently weaken the positive effects of authentic leadership on follower OCB across two studies. Furthermore, in Study 2, our findings suggest that organizational politics attenuate the positive impact of authentic leadership on follower job satisfaction and task performance. We discuss theoretical and practical implications.